Effects of aerobic exercise on the moods in elderly women - Antonio Baena Extremera; Pedro Jesús Ruiz Montero (FEADEF, 2011)
The intention of this descriptive study is to evaluate the degree of influence that the practice of aerobic physical activity exerts on the psychological well-being, the mental health and its repercussion in the moods. A sample formed by 63 participant women of the program of Physical Activity for elderly people has been used of the province of Malaga, with ages between the 60 and 79 years and that belongs to three inferior populations to 3,000 inhabitants, in a denominated region «Sierra de las Nieves». The participants complimented a sociodemografic questionnaire standardized and Profile of Moods States, POMS, in group a reduced version of 30 items in four factors: tension (8 ítems), vigor (8 ítems), fatigue (7 ítems) and friendship (7 ítems). The results obtained show that the four evaluated moods are not associate with the variables age and practice for physical reasons, whereas if the antiquity of practice of physical activity with the vigor and the variable disease is associate with the tension